Notions of Identity and Investment in Second Language Acquisition: Bangladeshi Indigenous Students’ Perspectives - Hossain, Ghazi Shahadat (Journal of NELTA, 2023)
Identity and investment are closely related to second language learning in many contexts. Many studies have been done on how second language learning aff ects the identity and investment of second language learners. Banking on the theory of identity, this article investigates how and why Bangladeshi students, belonging to indigenous communities, invest in second language learning and how their investment in L2 is linked to their agency. The study adopted an interpretative qualitative research paradigm and more precisely, utilized narrative inquiry as a research method to explore the lived experiences situated in a particular time, space and context. The findings exhibit that Bangladeshi ethnic students have made financial, physical, psychological and academic investments to own the linguistic, cultural and symbolic capital of English as a second language and such investment seems to be impacted by factors such as generating new identities (real or imagined), agency, neoliberalism and social justice. The research findings tend to have implications for second language teachers, researchers, SLA curriculum and material designers and other stakeholders in the Bangladeshi context or elsewhere.